2019
DOI: 10.15537/smj.2019.2.23913
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal stromal tumors

Abstract: Objectives: To evaluate the clinical presentations and immunohistochemical (IHC) properties of gastrointestinal stromal tumors (GISTs) and to compare them to internationally published data. Methods: Thirty-six patients diagnosed with GISTs between January 1997 and December 2015 were retrospectively studied in 2 tertiary hospitals. Immunohistochemical staining was carried out prospectively when it has not been completed fully at the beginning. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…Patients in our study most frequently presented with abdominal pain (78.7%). This finding is consistent with Al-Thani et al, in which abdominal pain was pres-ent in most of the patients (85%) (20), and Alghamdi et al, (16). In most reports, gastrointestinal bleeding was the most frequent clinical manifestation as reported by Miettinen et al, (21), Aghdassi et al, (12), and Zhao et al, (7).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Patients in our study most frequently presented with abdominal pain (78.7%). This finding is consistent with Al-Thani et al, in which abdominal pain was pres-ent in most of the patients (85%) (20), and Alghamdi et al, (16). In most reports, gastrointestinal bleeding was the most frequent clinical manifestation as reported by Miettinen et al, (21), Aghdassi et al, (12), and Zhao et al, (7).…”
Section: Discussionsupporting
confidence: 89%
“…In our study, the mean PFS was 20.75 months ranging between 7months and 39 months. The PFS was better in patients with gastric site primary which is similar to the results of Di Vita et al, (23), and Alghamdi et al, (16). Lillemoe et al, in a study of 133 patients with resected GIST also reported that survival was related to the tumor's site (26).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Small intestine GISTs express more often S100 and SMA. SMA is also a negative prognostic factor in localized tumors (there is a direct correlation between its positivity and disease relapse) ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Symptomatic MD such as gastrointestinal bleeding, Meckel diverticulitis, perforation, and bowel obstruction can all be treated by resection of symptomatic MD. GIST accounts for less than 1% of all gastrointestinal malignancies, their most common location being the stomach [ 19 ].…”
Section: Discussionmentioning
confidence: 99%